2019
DOI: 10.1021/acs.jproteome.9b00429
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Biological Attributes of N-Glycan Isomers in Breast Cancer Brain Metastasis Using Porous Graphitic Carbon (PGC) Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS)

Abstract: Breast cancer is a leading cancer in women and is considered to be the second-most common metastatic cancer following lung cancer. An estimated 10–16% of breast cancer patients are suffering from brain metastasis, and the diagnostic cases of breast cancer brain metastasis are increasing. Nevertheless, the mechanisms behind this process are still unclear. Aberrant glycosylation has been proved to be related to many diseases and cancer metastasis. However, studies of N-glycan isomer function in breast cancer bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 44 publications
0
50
0
1
Order By: Relevance
“…An alternative chromatographic mode to RP-LC in glycopeptide analysis is to use porous graphitized carbon (PGC). PGC has been successfully applied in the isomeric separation of different N -glycopeptides [ 13 , 14 ]. Another chromatographic option for glycopeptide separation is hydrophilic interaction liquid chromatography (HILIC) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative chromatographic mode to RP-LC in glycopeptide analysis is to use porous graphitized carbon (PGC). PGC has been successfully applied in the isomeric separation of different N -glycopeptides [ 13 , 14 ]. Another chromatographic option for glycopeptide separation is hydrophilic interaction liquid chromatography (HILIC) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we demonstrated isomeric separation of permethylated O-glycans, free oligosaccharides, and GSL-glycans using a PGC-LC technique that has been previously shown to separate permethylated N-glycans [28][29][30][31]. Several separation techniques for O-glycans were used, including the utilization of ion mobility [34] and PGC-LC [34,35] for analysis of native O-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported the efficient isomeric separation of N-glycans previously [28][29][30][31]. Here, we demonstrate the separation of smaller glycans such as O-glycans, free oligosaccharides, and glycosphingolipid-glycans (GSL-glycans) using permethylation and PGC-LC-MS to resolve isomeric glycans at a high sensitivity.…”
Section: Introductionmentioning
confidence: 92%
“…Aberrant glycosylation has proved to be related to the progression of several diseases, making the aberrant glycan structures possible biomarkers [16,17]. Furthermore, in some diseases, the glycome differences are observed as changes in the abundance of specific glycans.…”
Section: Isomeric Glycan Structures and Their Important Role In Biolomentioning
confidence: 99%
“…The results showed a high abundance of sialylated glycan isomers along with significant expression alterations in the brain cancer cell line and the breast cancer cell lines capable of brain metastasis, suggesting a relationship between sialylated glycan isomers and breast cancer brain metastasis. Moreover, they found that an increase of α2,6 linkage favors the passage of breast cancer cells through the blood–brain barrier, facilitating this type of cancer [16]. Anugraham et al.…”
Section: Isomeric Glycan Structures and Their Important Role In Biolomentioning
confidence: 99%